Analysis of vibrations of the working body of the vibrating separator in the resonant mode - Smetankina, Natalia; Misiura, Ievgeniia; Misiura, Serhii (Modeling, Control and Information Technologies: Proceedings of International scientific and practical conference, 2025)
This paper analyzes the nonlinear vibrations of the working body of a vibrating separator in resonant modes, focusing on the redistribution of energy between oscillation coordinates. Using the asymptotic averaging method, approximate solutions and auxiliary equations are derived to study the spatial stability of oscillations under combination resonances. It is shown that resonance relations involving the sum of natural frequencies and the excitation frequency do not disturb the planned technological process, ensuring stable operation of vibratory grain cleaning machines. The obtained results define parameter conditions that ensure stable operation of vibratory grain cleaning machines with helical oscillations of the working body. У цій роботі аналізуються нелінійні коливання робочого тіла вібраційного сепаратора в резонансних режимах з акцентом на перерозподіл енергії між координатами коливань. За допомогою методу асимптотичного усереднення отримано наближені розв'язки та допоміжні рівняння для дослідження просторової стійкості коливань при комбінованих резонансах. Показано, що резонансні співвідношення, що включають суму власних частот і частоту збудження, не порушують запланований технологічний процес, забезпечуючи стабільну роботу вібраційних зерноочисних машин. Отримані результати визначають умови параметрів, що забезпечують стабільну роботу вібраційних зерноочисних машин із гвинтовими коливаннями робочого тіла.